2016
DOI: 10.1111/1556-4029.13014
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Drug Overdoses in New Mexico: A 5‐year Retrospective Review

Abstract: To better understand the changing toxicology trends in suicidal drug overdoses in the setting of an increased national trend of multidrug overdoses, a retrospective review of electronic records from New Mexico's Office of the Medical Investigator database was performed between 2008 and 2012 to assess the drug type and current risk factors in suicide deaths. Information on demographics, circumstances, suicide risk factors, toxicology findings, and death certificates was collected and analyzed. Three hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…that comprised the summary drug use variable on the results of prior meta‐analyses of specific categories of drugs and risk for MVC (Elvik, ) and suicide (Wilcox et al., ). Although Elvik () concluded that benzodiazepines also confer proximal risk for MVC, we excluded this drug category due to the high prevalence of prescription benzodiazepines (presumably for mood, anxiety, or sleep disorders) that may be expected in suicide decedents (Szymanski et al., ) which could serve to bias any comparisons with MVCs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…that comprised the summary drug use variable on the results of prior meta‐analyses of specific categories of drugs and risk for MVC (Elvik, ) and suicide (Wilcox et al., ). Although Elvik () concluded that benzodiazepines also confer proximal risk for MVC, we excluded this drug category due to the high prevalence of prescription benzodiazepines (presumably for mood, anxiety, or sleep disorders) that may be expected in suicide decedents (Szymanski et al., ) which could serve to bias any comparisons with MVCs.…”
Section: Methodsmentioning
confidence: 99%
“…Decedents with missing or out‐of‐range data on age, sex, or ethnicity, or that did not have drug toxicology results, were excluded from analyses. Poisoning suicides (i.e., overdoses) were also excluded from analyses to minimize the potential that a drug (e.g., opiate) was deliberately taken to hasten death (Szymanski et al., ). Descriptive data on specific drug categories (e.g., cocaine) were reported and featured in post hoc analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The article by Szymanski et al (1) is both interesting and informative. They studied the drug type and current risk factors in suicide deaths, via a review of records from New Mexico's Office of the Medical Investigator database between 2008 and 2012.…”
Section: Sirmentioning
confidence: 98%
“…Szymanski et al believe that toxicology information will assist in creating public awareness and provide a framework to support targeted efforts to attempt to prevent future suicides. They also allude to a dilemma, for example, although it is well known that chronic pain alone is associated with an increase in suicidal thoughts and attempts and can be considered a predictor for suicide, the majorities of overdose deaths associated with chronic pain are deemed accidental in manner (1).…”
Section: Sirmentioning
confidence: 99%
“…Pessoas idosas e crianças são os grupos mais afetados do processo de medicalização de experiências humanas normais 5,6 . O aumento do uso de benzodiazepínicos está associado com o risco no desenvolvimento de muitas doenças e acidentes como dependência química 1 , overdose 7 , intoxicações fatais 8,9 e acidentes de trânsito 10 . O uso indiscriminado de benzodiazepínicos resulta em altos custos em tratamentos de saúde, diminuição da produtividade, redução da qualidade de vida relativa a saúde e mortalidade.…”
Section: Introductionunclassified